Incentives for disclosure of accounting information in public sector: A literature survey - Abu Bakar, Nur Barizah; Saleh, Zakiah (EuroJournals Publishing, 2011)
The purpose of the research is to conduct a literature survey of studies on factors that support or hinder disclosure of accounting information in public sector entities. The articles were reviewed across six aspects, namely: the (i) publication year, (ii) country of publication, (iii) journal of publication, (iv) type of government sector, (v) independent variable being studied, and, (vi) sample size. This literature survey provides a framework (developed from gaps in previous research) to public sector accounting research on the field of disclosure incentives.